2017
DOI: 10.3892/mmr.2017.7369
|View full text |Cite
|
Sign up to set email alerts
|

GATA4 is highly expressed in childhood acute lymphoblastic leukemia, promotes cell proliferation and inhibits apoptosis by activating BCL2 and MDM2

Abstract: Members of the GATA‑binding factor protein family, including GATA1, GATA2 and GATA3, serve an inhibiting role in leukemia. The present study demonstrated that GATA4 was upregulated in children with acute lymphoblastic leukemia (ALL). Results from a number of functional experiments, including cell proliferation analysis, cell cycle analysis, cell apoptosis assay and Transwell migration and invasion analyses, have suggested that high expression of GATA4 may facilitate proliferation and metastasis, and suppress a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…INHA expression alterations have been observed in p53 mutated adrenocortical tumors and INHA was suggested to be a contributing factor to tumorigenesis in these cancers [141]. One of the most characterized transcriptional activators of INHA is GATA4 [142], which can also regulate p53 in cancer and could contribute to the different survival outcomes observed for INHA in p53 mutated cancers versus wild-type p53 cancers [143,144]. INHA's link to functional outcomes in the background on p53 mutations remains to be fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…INHA expression alterations have been observed in p53 mutated adrenocortical tumors and INHA was suggested to be a contributing factor to tumorigenesis in these cancers [141]. One of the most characterized transcriptional activators of INHA is GATA4 [142], which can also regulate p53 in cancer and could contribute to the different survival outcomes observed for INHA in p53 mutated cancers versus wild-type p53 cancers [143,144]. INHA's link to functional outcomes in the background on p53 mutations remains to be fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…GATA4 mRNA expression is upregulated in pancreatic cancer cell lines and tissues [25], and downregulation of GATA4 expression increases drug sensitivity in cancer cells [28]. GATA4 can decrease P53 protein expression by transcriptionally activating the expression of MDM2 [29], the primary negative regulatory factor of the P53 protein that induces p53 ubiquitination and degradation [30]. GATA4 is also highly expressed in most hepatoblastomas and correlates with a mesenchymal, migratory phenotype in hepatoblastoma cells by regulating the expression of ADD3, AHNAK, and IGFBP1 [31].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, GATA4 has been proven to regulate the proliferation capability of a variety of cell types, such as cardiomyocytes, small intestinal epithelial cells, follicular granulosa cells, and leukemia lymphocytes [20][21][22][23][24]. However, regarding the VSMC, only two studies concerning human pulmonary artery SMCs and mouse aortic SMCs were reported so far [18,19].…”
Section: Discussionmentioning
confidence: 99%